A charge: funcionamento e efeitos de sentido em atividades escolares, leitura, pesquisa e produção textual - Dagostim, Cristiane Gonçalves (2009)
This research is based on the French theory segment of discourse analysis, especially through the perspective of the works developed by Orlandi, and it has taken into consideration the methodology of field work delineated at Santa Catarina Educational Curriculum (1998). It has therefore, as an objective, to verify the possibility of using charge as discourse genre as a teaching subject and investigating the effects of meaning (including the metaphorical aspects) of discourse found in the works developed by the students, thus how the charges functions and how they are formed. The research was carried out in a private elementary and secondary school, more specifically during writing classes. In order to be able to carry the research out, a variety of tasks were applied in three different groups in 8th grade during the third and fourth bimester of 2008. It was developed with the students activities based on thematic charges designed by the cartoonist Zé Dassilva that were published on Diário Catarinense Newspaper in 2008. The studies evolved in various steps: writing development, questioning the genre that has being used, analysis and production of charges, oral and written presentations of the works. The results of using discursive genre, in this case charge, in teaching shows that: a) it is largely relevant, as it stimulates critical thinking among the students; b) offers reflection about the use of metaphors and metaphorical effects that are obtained by the association of verbal and non-verbal language; c)helps to improve writing texts, especially the argumentative ones, as in chronicles; d) engage students in the learning-teaching process, as we notice that they conduct the classes themselves through discussions, therefore the teacher becomes more of a mediator.